NR2F1-AS1 Promotes Pancreatic Ductal Adenocarcinoma Progression Through Competing Endogenous RNA Regulatory Network Constructed by Sponging miRNA-146a-5p/miRNA-877-5p - Luo, Dong; Liu, Yunfei; Li, Zhiqiang; Zhu, Hongwei; Yu, Xiao (Frontiers in Cell and Developmental Biology, 2021)
The role of NR2F1-AS1 in pancreatic ductal adenocarcinoma (PDAC) remains unknown.Therefore,we aimed to investigate the biological mechanism of NR2F1-AS1 in PDAC.The expression of NR2F1-AS1 was measured by using microarray data and real-time PCR.The effects of NR2F1-AS1 knockdown on proliferation,cell cycle progression,invasion in vitro and tumorigenesis in vivo were investigated.The mechanism of competitive endogenous RNAs was determined from bioinformatics analyses and validated by a dual-luciferase reporter gene assay.Potential target mRNAs from TargetScan 7.2 were selected for subsequent bioinformatics analysis.Key target mRNAs were further identified by screening hub genes and coexpressed protein-coding genes of NR2F1-AS1.NR2F1-AS1 was highly expressed in PDAC,and the overexpression of NR2F1-AS1 was associated with overall survival and disease-free survival.The knockdown of NR2F1-AS1 impaired PDAC cell proliferation,migration,invasion and tumorigenesis.NR2F1-AS1 competitively sponged miR-146a-5p and miR-877-5p,and low expression of the two miRNAs was associated with a poor prognosis.An integrative expression and survival analysis of the hub genes and coexpressed protein-coding genes demonstrated that the NR2F1-AS1--miR-146a-5p/miR-877-5p--GALNT10/ZNF532/SLC39A1/PGK1/LCO3A1/NRP2/LPCAT2/PSMA4 and CLTC ceRNA networks were linked to the prognosis of PDAC.In conclusion,NR2F1-AS1 overexpression was significantly associated with poor prognosis.NR2F1-AS1 functions as an endogenous RNA to construct a novel ceRNA network by competitively binding to miR-146a-5p/miR-877-5p,which may contribute to PDAC pathogenesis and could represent a promising diagnostic biomarker or potential novel therapeutic target in PDAC.